The Influence of Green Accounting and Capital Structure on Financial Performance: Does Audit Quality Matter? - Tiara Mardiana; Mulyadi Noto Soetardjo (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study was conducted with the aim of testing and analyzing the effect of Green Accounting and Capital Structure on Financial Performance with Audit Quality as moderating variable in ASEAN’s mining companies for the period of 2019-2023. The population in this study were mining companies listed on stock exchanges in ASEAN in 2019-2023. The sampling method used is purposive sampling technique. The data source used is secondary data. The data analysis method used in this research is regression analysis. The results of testing the hypothesis of this study indicate that Green Accounting has a positive and significant effect on Financial Performance, Capital Structure has no effect on Financial Performance and Audit Quality does not moderate the relationship of Green Accounting and Capital Structure towards Financial Performance. The results implied that by implementing Green Accounting the company will have a good image and reputation to attract more customers, investors and business partners so that this increase in reputation can increase sales and profitability. The results also indicate that the possibility of companies relying more on good performance or other things in generating profits without seeing how the proportion of financing (capital structure) utilized. Also, the results of this study show that investors, customers and business partners are likely to see good corporate governance to invest or to cooperate without considering how the company's audit quality level is.